Cervical cancer: primary or secondary level prevention? - Hyppólito, Silvia Bomfim; Franco, Eugênio S.; Franco, Rosana G.F.M.; Albuquerque, Celina M.; Nunes, George C. (Brazilian Journal of Sexually Transmitted Diseases, 2023)
One of the goals of the Health Ministery is to decrease cervical cancer mortality through a cervical cancer screening program using Papsmear todetect early the disease and provide adequate treatment of lesions – secondary level prevention program. It's been proved on literature that cytologyhas a high specificity but a low sensitivity, and so, it is not a good screening test for a high prevalence disease, such as the HPV infection and its last consequence, cervical cancer, here in Brazil. More sensitive and low cost screening tests such as Visual Inspection with acetic Acid – VIA andCervicography are being proposed as adjunctive tests to cytology. In the case now presented, the importance of such strategies is reinforced, besidesmore effective diagnostic and therapeutics conducts are recommended.